Performance and Efficiency Comparison of Human Waste Biogas and LPG Production in Modified Water Pump Engines - Anggrainy, Rani Anggrainy; Afiah, Syifa Kawakib Nurul; Latiep, Abdul; Sukrawan, Yusep; Noor, Ridwan Adam Muhamad; Nurhaliza, Tiana; Fauzi, Virgi Ahmad; Abdurrahman, Fajar (Universitas Negeri Jakarta, 2025)
As daily needs and fuel prices continue to rise and non-renewable natural resources diminish, alternatives are needed to replace these energy sources with renewable energy. Data from the National Energy Council shows that in Indonesia, only 16.358 household biogas digester units have been installed, or about 1.6% of the total potential that can be utilized. This research aims to compare the performance of biogas from human feces with liquefied petroleum gas (LPG) as fuel for water pump engines. The method used is experimental, involving the modification of the carburetor on the water pump engine, followed by direct measurement and analysis of the water pump results using variations of biogas and LPG fuels. A literature review indicates that biogas has great potential as a renewable energy source, but its utilization in Indonesia remains very limited. In this study, the test variables include variations in pump speed at 3800, 5300, and 6600 rpm. The test results show that the mass flow rate of biogas compared to LPG yields the highest discharge at 6600 rpm (0.118: 0.150 m³/s). For both biogas and LPG fuels, the maximum shaft power of the water pump engine reaches 3.9 kW at 6600 rpm. The maximum waterpower generated by the water pump engine using biogas and LPG is 1.26 kW and 1.6 kW at 6600 rpm, respectively, while the maximum efficiency reaches 32% with biogas and 41% with LPG. Therefore, the higher the water pump engine speed, the higher the values of shaft power, engine power, discharge, and efficiency. The efficiency ratio comparison between biogas and LPG at 6600 rpm is 3:4.